Indole-3-acetic acid promotes wound healing of potato tubers by activating auxin signaling and phenylpropanoid metabolism - Lirong Yu; Tongtong Cui; Pengdong Xie; Botao Bai; Ruirui Yang; Ye Han; Yi Wang; Xin Li; Yang Bi; Dov Prusky (Postharvest Biology and Technology, 2026)

Alginate-derived oligosaccharides obtained from enzymatic hydrolysis of Laminaria improve temperature adaptability and increase bioactive compound yield in Phaeodactylum tricornutum - Xingkai Che; Dingning Fan; Ruirui Ding; Litao Zhang; Benwei Zhu; Yongfu Li (Bioresource Technology, 2026)

Evaluation and calculation of the 239Pu(n,f) cross section up to 200 MeV - Bo Gao; Changlin Lan; Bo Xie; Kuozhi Xu; Yanliang Chang; Muntazir Mehdi; Fanmin Zeng; Xiaonan Huang; Jianglong Pan; Ruirui Xu; Yue Zhang; Shilong Liu; et al. (Annals of Nuclear Energy, 2026)

Dual-driven TBM attitude control method based on bidirectional mechanical control laws and tunneling parameter interaction - Jiwen Wang; Benchao Liu; Yaxu Wang; Ruirui Wang; Ningbo Li (Tunnelling and Underground Space Technology, 2026)

Numerical simulation of thermal-hydraulic-chemical multi-physical field coupling for large-scale experimental models of CO2 hydrate sequestration - Lei Wang; Xianjie Yan; Yang Ge; Ruirui Li; Zhaoran Wu; Jinyan Lan; Jiefeng Liu (Fuel, 2026)

Biosensor-driven adaptive laboratory evolution and modular pathway engineering for high-level production of nicotinamide mononucleotide in yeast - Ruirui Shi; Qiancheng Han; Yingxue Xu; Lei Li; Fuping Lu; Yixun Jiang; Zhengqiang Jiang; Hui-Min Qin (Bioresource Technology, 2026)

1,12-cyclic-apelin-12 counters vascular smooth muscle cell proliferation and atherosclerosis through inhibiting aerobic glycolysis - Ruirui Lu; Xiaosi Zhou; Huimei Liu; Sisi Fan; Xiaohui Huang; Fengting Guo; Bin Huang; Linxi Chen; Lanfang Li (Toxicology and Applied Pharmacology, 2026)

Cold plasma treatment enhanced defense responses against gray mold and enhances postharvest quality in cherry tomatoes - Miaomiao Ge; Ruirui Qiu; Xinzhi Fang; Ling Li; Jian Guo (Food Research International, 2026)

Cinnamic acid grafting unlocks high-rate sodium storage in hard carbon - Changhong Li; Liujie Liang; Hairong Gong; Minyi Zou; Yingxia Dong; Pengcheng Xue; Bomao Huang; Liang Ma; Luyi Chen; Ruirui Zhao; Qifeng Zheng (Chemical Engineering Journal, 2026)

Rapid aerobic sludge granulation by short-term in-situ chitosan dosing: Performance, mechanism and microbial response - Fengfan Yu; Ruirui Wang; Yanhang Wang; Mengjie Qian; Jintao Sun; Jinwen Song; Jinte Zou; Jun Li (Bioresource Technology, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

A hybrid SEM-MTF-DRM method for dynamic soil-structure interaction analysis - Ruirui Nan; Hongjing Li; Haojie Xing (Soil Dynamics and Earthquake Engineering, 2026)

Mg/Ca ratio-regulated phase differentiation of microbially derived CaCO3 and its effects on Cu2+, Cd2+, and Pb2+ immobilization - Kaiming Hu; Yanyang Zhao; Yishui Han; Zuozhen Han; Ruirui Meng; Xiao Gao; Jie Li; Na Guo (Journal of Hazardous Materials, 2026)

Selective cleavage of Cβ-O-containing Cα-Cβ bond on Cu-Ni3S2 for electrocatalytic glycerol oxidation to formic acid - Ruirui Xu; Xinti Yu; Ce Fu; Lina Li; Zhangxing Chen; Heng Zhao (Chemical Engineering Journal, 2026)

Achieving 96.6% energy-storage efficiency in Nd-doped tungsten-bronze ceramics through A-site vacancy engineering - Zhihong Wang; Yangfei Gao; Bian Yang; Mei Bai; Xiangran Pei; Hai Ci; Ruirui Kang; Junbo Xu; Yingying Zhao; Mengyao Guo; Fei Li; Xiaojie Lou (Chemical Engineering Journal, 2026)

Robust photothermal regulation in large-area smart windows enabled by bimetallic NiCo hydroxide with layered structure - Yi Gao; Xiaoting Li; Qiaodeng Ding; Pengyang Lei; Xinyi Wang; Chengyu Hu; Ruirui Ren; Jinhui Wang; Guofa Cai (Chemical Engineering Journal, 2026)

Bioinformatics analysis and differential tissue expression of the IGFBP4 gene in beef cattle - Ruirui Song; Bingzhi Li; Sihu Wang; Maryam Alenize; Yanqing Zhao; Aaishah M. H. Kaabi; Afnan O. Deebani; Wasimah AlShammari; Dalal Alenizi; Dalal Alardan; Wenzhen Zhang (Protoplasma, 2026)

Historical grazing intensity determines the response patterns of plant community and soil nutrient stocks to grazing exclusion in a temperate meadow steppe - Haonan Guo; Xiaoping Xin; Jiquan Chen; Phil J. Murray; Maira Kussainova; Wei Fang; Zhigang Zhao; Hui Li; Cuixia Jiang; Yufan Si; Amarjargal Amartuvshin; Alim Pulatov; et al. (Agriculture, Ecosystems & Environment, 2026)

Trade-offs among pear yield, fruit quality, and reactive nitrogen losses under water–nitrogen management across contrasting soil textures - Yanlong Li; Ruirui Du; Mingde Sun; Yang Wu; Zhenxu Liang; Qinghua Wang; Jun Liu; Songzhong Liu (Journal of Environmental Management, 2026)

A comparative bioprocess for nutrient reclamation: Suspended versus immobilized Virgibacillus salexigens XYD drives struvite recovery from eutrophic saline water - Na Guo; Yueming Zhao; Shuqi Wang; Yanhong Zhao; Yudong Xu; Memon Kashif Ali; Huaxiao Yan; Hui Zhao; Zuozhen Han; Maurice E. Tucker; Chao Han; Yanyang Zhao; et al. (Journal of Environmental Management, 2026)

N and S co-doped graphene-based single-atom catalysts for highly efficient nitrate reduction - Jin-Hang Liu; Yu Sun; Xiaoduo Jiang; Huixiong Jiang; Ruirui Wang; Yawei Wang; Huixian Ye; Xiudong Chen; Li-Ming Yang (Fuel, 2026)

Novel mutation sites in yeast FAS enhance the production of C6–C10 fatty acids and their ethyl esters - Yupeng Wang; Junbao Gong; Xinyu Lu; Yanfang Chen; Ruirui Li; Ying Guo; Chunhong Sun; Xinjian Wang; Ying Zhou; Xiaole Wu; Yefu Chen (Food Bioscience, 2026)

Temperature-dependent KMnO4 oxidative decrosslinking for enhanced permeance and scaling resistance of polyamide nanofiltration membranes - Ning Ma; Ruirui Jiang; Jielin Shi; Xinwei Kang; Jinyu Li; Feiyue Ge; Feilong Zhang; Feiyong Chen; Daliang Xu; Xuewu Zhu (Desalination, 2026)

Construction of an Oral Vaccine Based on Multiple Antigens of African Swine Fever Virus Displayed on the Surface of Bacillus Subtilis Spores and Study of its Immune Effect in Rats - Tian Yang; Maomao Li; Zhuoxuan Wu; Jiahua Cheng; Ningyin Si; Weiping Du; Ruirui Wang; Yuhong Lyu (Current Microbiology, 2026)

Super-resolution multimodal spatial transcriptomics reveals an ovoid stem cell niche structuring de novo shoot regeneration - Xiehai Song; Shaoman Zhang; Zhiliang Yue; Yongqi Liu; Shanshan Chen; Yani Niu; Yan Shi; Hengjia Yang; Jiahao Xu; Yuanyuan Miao; Meizhi Xu; Yingxue Zhou; et al. (Molecular Plant, 2026)

Indium-doped CuSnO3 perovskite hybrids for chemiresistive CO sensing - Linyan Gu; Yangtao Qian; Yiting Liu; Miao Cheng; Tao Wei; Qianqian Liu; Ruirui Wang; Wanfei Li; Zhenxiao Fu; Haiyang Jiang; Zibo Li; Bo Liu; et al. (Chemical Engineering Journal, 2026)

The pivotal regulatory factor circ_0006956 promotes arsenic-induced lung carcinogenesis by enhancing the Warburg effect - Deqing Li; Xiaodong Zhou; Dunyu Cai; Haotian Xu; Xingcai Chen; Shengyi Yuan; Taoran Ning; Xiangyu Dong; Mengyao Li; Qiumei Liu; Ruirui Zhang; Wenyi Peng; et al. (Chemico-Biological Interactions, 2026)

Metabolic engineering of mannitol metabolism to improve protein production in Fusarium venenatum - Xizhen Liu; Longxue Ma; Ruirui Zhang; Yang Yang; Wuxi Chen; Liucheng Long; Yu Zheng; Demao Li (Systems Microbiology and Biomanufacturing, 2026)

Deep learning based behavioural monitoring and analysis of grazing sheep - Tianci Hu; Jinxing Li; Ruirui Yan; George Vlontzos; Wenxin Zheng; Xinwen Chen; Leifeng Guo (Biosystems Engineering, 2026)

Rhizosphere metabolic responses to soil acidification and their implications for nutrient uptake in eggplant - Tianqi Wang; Muhammad Awais; Xiaoyang Yu; Baiyi Bai; Zhen Wang; Ruirui Zhang; Lijie Yu; Dan Zhao; Xing Li; Ping Zhang; Roland Bol; Lijuan Yang (Rhizosphere, 2026)

Laponite-reinforced marine bioinspired injectable self-healing adhesive chitosan-based hydrogel for infected wounds - Ruirui Guan; Yuhui Su; Shanshan Li; Shuo Yang; Xiaoyun Li; Xiaoying Wang (Carbohydrate Polymers, 2026)

Comparative analysis of ecological corridor evolution and environmental quality in an urban small watershed: A case study of the Jiyu River, Hefei (2019–2024) - Guoxu Chen; Kaidi Yang; Ruirui Li; Li Cao; Xincheng Gao; Yongqi Fan; Kesheng Zuo; Li’ao Quan (Urban Ecosystems, 2026)

Transformation of microcrystalline and graphitization of particulate matter during DPF regeneration driven by non-thermal plasma: Mechanisms and reaction pathways - Yunxi Shi; Ruirui Ji; Yankang Huang; Xinyi Huang; Zhenguo Li; Jianbing Gao; Xiangyang Wang (Journal of Cleaner Production, 2026)

Ergothioneine and lactoferrin exert synergistic neuroprotective effects through the Tnfrsf12a/NF-κB signaling axis - Hui Li; Xiaoyu Wang; Yujie Xu; Zhibao Cheng; Ruirui Li; Jingyuan Xiong; Guo Cheng (Food Bioscience, 2026)

Discovery of juglone derivatives as potential nematicides by exacerbating oxidative damage - Xue Guo; Ruirui Zhao; Jie Wang; Yan Li; Xiuhai Gan (Pesticide Biochemistry and Physiology, 2026)

Mapping ecosystem service supply–demand interactions using spatial clustering: Insights for sustainable grassland management - Xiaotian Gao; Frank Yonghong Li; Xiaoping Xin; Ruirui Yan (Journal of Environmental Management, 2026)

Catalytic liquefaction of pig manure in ethanol: Yield and properties of bio-oil - Qingdan Wu; Siyu Huang; Qianlan Li; Xiaochen Zheng; Wei Liu; Ruirui Zhu; Jialong Tang; Binbin Dai; Yingying Mo; Likun Zhan; Jie Xiong; Zhihua Xiao (Biomass and Bioenergy, 2026)

Grazing Stocking Rate and Rainfall Jointly Regulate Soil Methane Uptake in a Temperate Meadow Steppe, but Do Not Reverse Net Methane Emissions - Tianqi Yu; Yu Zhang; Miao Wang; Chu Zhang; Jiquan Chen; Yuchun Yan; Xu Wang; Changliang Shao; Xiaotao Lü; Hui Li; Linghao Li; Lianhai Wu; et al. (Global Change Biology, 2026)
Grasslands are widely recognized as important sinks of methane (CH 4 ). However, their CH 4 uptake capacity has been increasingly weakened driven by human activities and changes in precipitation regimes. In particular, the rapid expansion of livestock grazing can lead to substantial increases in CH 4 emissions. For the Eurasian grasslands that have been subject to long‐term grazing, how well they currently function and will continue to function as CH 4 sinks under the changing precipitation regimes remains uncertain. Here we conducted an 11‐year grazing‐gradient experiment to assess the combined effects of grazing intensity and precipitation variability on grassland CH 4 fluxes. We measured soil CH 4 uptake in a manipulative grazing experiment in both wet and dry years, estimated livestock‐derived CH 4 emissions, and examined a range of biotic and abiotic drivers, including vegetation attributes, soil properties, and microbial biomass, for short‐ (prior to the onset of the lagged response) and long‐term (the entire experimental period) influences on the dynamics of CH 4 uptake in temperate meadow grasslands. Over the long term, CH 4 fluxes are jointly regulated by precipitation and grazing, with overgrazing amplifying the suppressive effect of rainfall on CH 4 uptake. Soil CH 4 uptake showed a lagged response to grazing, which may have been triggered by extreme rainfall events. While moderate grazing sustained the long‐term CH 4 uptake, it fails to offset livestock‐derived CH 4 emissions. In the short term, CH 4 fluxes are primarily governed by grazing, whereas in the long term they are jointly regulated by precipitation and grazing intensity. These results offer a new perspective for understanding the source–sink CH 4 dynamics of grasslands in the context of ongoing climate change.

TANK-binding Kinase 1 regulates the intracellular survival of Brucella - Zhiqiang Li; Shuli Wang; Ruirui Li; Yanyan Cui; Jinliang Zhang; Junfang Hao; Huijun Zhang; Qifeng Li; Hui Zhang (Veterinary Microbiology, 2026)

Clonidine compromises human sperm functions - Xuchang Liu; Yanfan Cui; Ruirui Qian; Yixuan Li; Zeyu Hu; Houyang Chen; Yufeng Yuan; Tao Luo (Reproductive Toxicology, 2026)

The papain-like cysteine proteases (PLCP) in tomato: Identification, expression analysis, and functional characterization of SlRD19B under salt stress - Jiaxuan Zhu; Ruirui Yang; Yan Li; Ruili Lv; Huimin Li; Yao Yao; Yushi Luan (Plant Science, 2026)

Identifying the genesis and evolution of geothermal water in the coal mining area, North China: Insights from hydrochemistry and δ2H, δ18O, δ13C, δ34S and 87Sr/86Sr isotopes - Jie Zhang; Herong Gui; Luwang Chen; Manli Lin; Huifang Rong; Jun Li; Ruirui Li; Mingda Cao (Geothermics, 2026)

An ab initio kinetic study on H-abstraction reactions from methyl butenoates by NO2 - Ruirui Kong; Zhiheng Zhu; Yaozong Duan; Fashe Li; Hua Wang (Fuel, 2026)

N-halamine-grafted MIL-125-NH2(Ti) as a long-lasting chlorine reservoir for round-the-clock decontamination of Aspergillus aerosols - Ruirui Hou; Hao Yang; Fengming Hou; Yihang Li; Zhipeng Guo; Jin Li; Wei Wei; Ang Wei (Chemical Engineering Journal, 2026)

Biomineralization induced by Shigella dysenteriae JS3: The mechanism, and the differences between biotic and abiotic whewellite and struvite - Na Guo; Jizheng Qiao; Shuhua Zhang; Shengzhe Gao; Yanhong Zhao; Chao Han; Hui Zhao; Yanyang Zhao; Xiao Gao; Ruirui Meng; Bin Cao; Yu Li; et al. (Chemical Geology, 2026)

Distribution and source of plutonium in seawater columns of the oligotrophic region in the North Pacific - Ruirui Wang; Yukun Li; Deyu Wang; Xiaomin Wei; Yongjing Guan; Xibin Han; Zhiyong Liu (Marine Pollution Bulletin, 2026)

Functional analysis of SlCDPK12 and its interacting protein SlACS11 in the regulation of tomato resistance to Phytophthora infestans - Yan Li; Jiaxuan Zhu; Ruili Lv; Zhengjie Wang; Huimin Li; Ruirui Yang; Yushi Luan (Journal of Plant Physiology, 2026)

Precision detection and geolocation of missed pre-tassels in hybrid maize seed production using UAV-based deep learning - Chenchen Ding; Ruirui Zhang; Jiangtao Qi; Yuxin Xie; Tongchuan Yi; Longlong Li; Mingqi Wu; Weirong Zhang; Zhiyuan Bao (European Journal of Agronomy, 2026)

Cuproptosis and Its Impact on Cardiovascular Health: Mechanisms and Therapeutic Opportunities - Xiaohui Huang; Liwen Wang; Huimei Liu; Ruirui Lu; Lanfang Li (Cardiovascular Toxicology, 2026)

Liquid-in-liquid printing and machine learning assisting the achievement of omni-directional, self-encapsulated flexible strain sensors - Ruirui Zhang; Li Wang; Weiguang Su; Jin Du; Zhenyu Li; Jiangdong Ji; Xujiang Chao (Chemical Engineering Journal, 2026)

Identification of quantitative trait loci qPL6 for petiole length in soybean - Weiwei Fan; Lindong Wang; Wenxuan Huang; Jia Liu; Bing Li; Jingyu Peng; Ruirui Ma; Ran Xu; Lianjun Sun (Theoretical and Applied Genetics, 2026)

Changes in plant community composition and soil resource drive jointly fine root productivity response to grazing in a meadow steppe - Hui Li; Changliang Shao; Yuguang Ke; Xiaoping Xin; Ziwei Tao; Yufan Si; Haonan Guo; Cuixia Jiang; Ruirui Yan; Guozhen Du; Zihao Li; Feng Liu (Plant and Soil, 2026)

Corrigendum to “Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region” [Sci. Total Environ. 946 (2024) 174054] - Xiaoping Xin; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; Ruirui Yan; et al. (Science of The Total Environment, 2025)

Degradation mechanism of diesel particulate emissions induced by non-thermal plasma - Yunxi Shi; Ruirui Ji; Xinyi Huang; Zhenguo Li; Jianbing Gao; Pan Wang; Jun Wang; Yixi Cai; Lei Yu (Journal of Environmental Chemical Engineering, 2025)

Bimetallic chloride in situ etching of NiFe alloy substrate to synthesize porous coral structure catalyst for efficient oxygen evolution reaction - Yu Zhang; Yaoxia Yang; Biaobiao Lu; RuiRui Zhang; Fuxing Zhou; Dongfei Sun; Qingtao Wang; Jian Li; Ziqiang Lei (Fuel, 2025)

Unveiling the oxidation-reduction mechanism of the Arsenazo III-U(VI) complexes by synergistic electron beam irradiation and Cu-Fe MOFs: Combined kinetic and DFT studies - Ruirui Wang; Xiaomao Zhou; Dan Liu; Jiahui Li; Long Zhao; Zhen Dong; Buri Qi; Miao Yang (Chemical Engineering Journal, 2025)

Ecological strategies of evergreen and deciduous woody species: including nitrogen and phosphorus allocation among organs, and element-based network - Xueqin Li; Xiaoping Chen; Yongjiao Zhou; Ruirui Fan; Peter B. Reich; Dandan Hu; Quanlin Zhong; Dongliang Cheng (Oecologia, 2025)

Cornus officinalis polysaccharides nano-selenium exhibits anti-fatigue effects by regulating gut microbiota in mice - Jianrui Sun; Ruirui Ren; Jinglan Li; Jiaqi Fan; Linlin Yao; Shanshan Tie; Jie Zhang; Dahong Wang; Shaobin Gu (Food Bioscience, 2025)

Cation engineering enables visible tunable tricolor long persistent luminescence in Cu2+-activated phosphors for advanced information encryption - Xingyang Peng; Rongmao Li; Yanzhi Zhang; Hao Guo; Kang Wang; Can Yuan; Xiang Guo; Chaoyong Deng; Ruirui Cui (Chemical Engineering Journal, 2025)

The receptor-like kinase SlLRR-RLK94 as a positive regulator of tomato resistance to Phytophthora infestans - Jiaxuan Zhu; Yan Li; Ruirui Yang; Zhiyuan Xue; Ruili Lv; Hongbo Wei; Zhengjie Wang; Ruiming Wang; Yushi Luan (Plant Cell Reports, 2025)

National-scale genomic diagnosis of rare diseases in China - Xiaodong Luan; Ye Jin; Liping Guan; Peng Liu; Hailong Feng; Dingding Zhang; Jingdan Chen; Weida Liu; Fangyuan Li; Anqi Wang; Kun Zhao; Ruirui He; et al. (Science Bulletin, 2025)

A multi-sensor, phenology-based approach framework for mapping cassava cultivation dynamics and intercropping in highly fragmented agricultural landscapes - Xincheng Wang; Qinfei Wang; Hongyan Lai; Zhenwen Zhang; Ting Yun; Xiaojing Lu; Guizhen Wang; Shangye Lao; Qi Liao; Saiqing Lu; Ruirui Chen; Shijing Fang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

A comprehensive investigation of mechanical mixing-thermal activation for CaO-based adsorbent with coal fly ash as a stabilizer - Ruirui Zhang; Xuehua Shen; Yongjia Liang; Han Hua; Gang Li; Feng Yan; Zewei Quan; Zuotai Zhang (Chemical Engineering Journal, 2025)

Large electrocaloric temperature change in lead-free (Bi0.47Na0.47Ba0.06)TiO3-based ceramics via regulating non-ergodic - ergodic transition - Junwen Mei; Mei Bai; Yangfei Gao; Ruirui Kang; Xiangran Pei; Haichao Hu; Junjie Xiong; Jiantuo Zhao; Feng Li; Dezhen Xue; Zhongliang Lu; Xiaojie Lou (Chemical Engineering Journal, 2025)

Atrazine-induced hippocampal neurotoxicity: Involvement of Drp1-mediated mitochondrial fission - Jingran Yang; Ling Qi; Cheng Zhang; Ruirui Ding; Haoran Bi; Peng Li; Zhipeng Qi; Qiao Niu; Weiyi Song; Jianan Li (Chemico-Biological Interactions, 2025)

Engineering Komagataella phaffii cell factories for the production of chondroitin sulfate A with high sulfation degree - Haibo Xiong; Xiaogang Yang; Weijiao Zhang; Litao Hu; Gege Liu; Guocheng Du; Jian Chen; Jianghua Li; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2025)

Dual AIE combination strategy: An efficient BioAIE active photosensitizer derived from berberine for bacterial elimination - Zhi-Hao Li; Daran Li; Yuanbo Li; Ruirui Li; Hongtao Kong; Ye Qu; Yuequan Wu; Jifeng Liu; Shangshang Qin; En Zhang; Yong-Qiang Tu (Chemical Engineering Journal, 2025)

Establishment of reference intervals for serum immunoglobulin G N-glycosylation features in healthy Chinese adults: a nationwide survey in the framework of predictive, preventive, and personalized medicine - Changyu Liu; Yinghao Wang; Xingang Li; Xiaojia Xu; Ruirui Xu; Cuihong Tian; Zhixian Chen; Xinxia Lu; Yuejin Li; Meng Wang; Zhaoyang Tang; Xueyu Chen; et al. (EPMA Journal, 2025)

Exogenous spermidine promotes the formation of the closing layer at potato tuber wounds by inducing polyamine synthesis and phenylpropanoid metabolism - Ying Wang; Ruirui Yang; Qihui Wang; Pengdong Xie; Xiaojing Wang; Yongcai Li; Dov Prusky; Ye Han; Yang Bi (Postharvest Biology and Technology, 2025)

Cytokinin signaling pathway involved in 6-BA-induced wound healing in potato tubers - Ruirui Yang; Qihui Wang; Ying Wang; Xuejiao Zhang; Zixiong Ye; Chunwei Han; Jiaojuan Wang; Yongcai Li; Dov Prusky; Yang Bi; Ye Han (Postharvest Biology and Technology, 2025)

A new strategy of one-step sequential extraction of copper cyanide complex ions from cyanide leach solutions - Weichao Li; Wengang Liu; Wenbao Liu; Ruirui Zhang; Shuaichao Wang (Minerals Engineering, 2025)

Assessment of the immune-developmental toxicity risk of the hygienic insecticide dimefluthrin in zebrafish (Danio rerio) model - Ruirui Li; Yang Yu; Wenxuan Cheng; Qingfeng Li; Wenping Xu; Jiagao Cheng; Liming Tao; Yang Zhang (Journal of Environmental Management, 2025)

Exploring the mechanisms of hippocampal neurotoxicity induced by cypermethrin: Insights from integrated miRNA-seq and mRNA-seq analysis - Jingran Yang; Ruirui Ding; Ling Qi; Haoran Bi; Jianan Li (Environmental Toxicology and Pharmacology, 2025)

Optimization of unmanned aerial vehicle operational parameters to maximize fertilizer application efficiency in rice cultivation - Xue Xia; Ruirui Zhang; Li Ma; Jiaying Su; Tongchuan Yi; Linhuan Zhang; Xiaoyu Chen (Journal of Cleaner Production, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

Long-term reconstruction of NO2 photolysis rate coefficients using machine learning and its impact on secondary pollution: A case study in a megacity of the Sichuan Basin, China - Tong Li; Song Liu; Dongyang Chen; Ruirui Zhang; Hefan Liu; Danlin Song; Qinwen Tan; Hongbin Jiang; Li Zhou; Fumo Yang (Atmospheric Pollution Research, 2025)

A genomic compendium of cultivated food-derived lactic acid bacteria unveils their contributions to human health - Hao Jin; Keyu Quan; Lijun You; Lai-Yu Kwok; Teng Ma; Yalin Li; Xuan Shi; Xin Su; Ruirui Lv; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2025)

Short-term PS-NP exposure in early adulthood induces neuronal damage in middle-aged mice via microglia-mediated neuroinflammation - Shan Shan; Dong Cheng; Hui Li; Wenhuan Yao; Ruirui Kou; Jing Ji; Na Liu; Tao Zeng; Xiulan Zhao (Journal of Hazardous Materials, 2025)

Effect of alkaline-thermal pretreatment on biodegradable plastics degradation and dissemination of antibiotic resistance genes in co-compost system - Wenyue Wang; Jianping Tao; Ruirui Pang; Linjie Zhang; Yuchen Zhang; Yinglong Su; Weiying Li; Seungkwan Hong; Hyunook Kim; Min Zhan; Bing Xie (Journal of Hazardous Materials, 2025)

Involvement of the miR156/SPLs/NLP7 modules in plant lateral root development and nitrogen uptake - Ruirui Xu; Peng Wang; Yunning Pang; Huilian Liu; Tianpeng Zhang; Ying Li; Shizhong Zhang (Planta, 2025)

Energy absorption behavior of a bottom-supported thin-walled steel tube impacted by rockfall - Fuyou Huang; Luqing Zhang; Jian Zhou; Zhenhua Han; Song Wang; Ruirui Li (Natural Hazards, 2025)

Identification of biomarkers associated with phagocytosis regulatory factors in coronary artery disease using machine learning and network analysis - Runan Jia; Zhiya Li; Yingying Du; Huixian Liu; Ruirui Liang (Mammalian Genome, 2025)

Shedding light on the shadows: Transparency challenge in background life cycle inventory data - Jing Guo; Ruiqiao Li; Ruirui Zhang; Jianchuan Qi; Nan Li; Changqing Xu; Anthony S. F. Chiu; Yutao Wang; Hiroki Tanikawa; Ming Xu (Journal of Industrial Ecology, 2025)
Life cycle assessment (LCA) hinges on the transparency and reliability of inventory data. However, the transparency of background life cycle inventory (LCI) data sources remains unexamined. This research assesses data transparency in mainstream LCI databases using a two‐step examination system based on source findability and accessibility. Six major databases (ecoinvent, GaBi, U.S. Life Cycle Inventory Database, European Life Cycle Database, Inventory Database for Environmental Analysis, and Chinese Life Cycle Database) were analyzed by sampling processes and tracing their sources. The results reveal widespread transparency issues, with only 40%–60% of sampled processes having findable sources and <5% being fully accessible in certain databases. Incomplete documentation and complex cross‐referencing between processes and sources posed key barriers. The lack of transparency undermines LCA credibility and necessitates reconstructing databases for enhanced traceability. Although a preliminary study, these findings highlight the challenge of data transparency and provide a methodology to evaluate databases. This drives collective action to uphold transparency standards, restoring trust in LCA as a sustainability decision‐making tool.

Alginate-derived oligosaccharides (AOS) enhance the biomass of Phaeodactylum tricornutum and fucoxanthin yield - Xingkai Che; Dingning Fan; Ruirui Ding; Haixing Wu; Yongfu Li (Journal of Applied Phycology, 2025)

Quercetin attenuates DEHP-induced pyroptosis and programmed necrosis in chicken duodenum through regulation of the TLR4/MyD88/NF-κB pathway - Ruirui Xie; Tong Xu; Yilin Yin; Meichen Liu; Chenxi Huang; Wenwen Zhang; Shu Li (Environmental Pollution, 2025)

Highly synergistic degradation of norfloxacin and outstanding elimination of antibiotic-resistant elements by a combined electro-Fenton/peracetic acid process under mild conditions - Ling Feng; Wentao Dong; Bowei Li; Qing Li; Zhijing Liu; Ruirui Feng; Stefanos Giannakis (Journal of Environmental Chemical Engineering, 2025)

The dynamics impact of phlorizin on gut microbiota and metabolites in an in vitro fermentation model - Dingzuo Ge; Luyao Zheng; Li Liu; Xin Chen; Jiawei Zhou; Han Ge; Liqiang Guo; Hua Hua; Ruirui Wang; Lei Zhang (Food Research International, 2025)

Warmer summers have the potential to affect food security by increasing the prevalence and activity of Actinobacteria - Yuanyuan Bao; Jan Dolfing; Zhiying Guo; Jie Liu; Xianzhang Pan; Xiaodan Cui; Yuanyuan Wang; Yang Jin; Lixia Zhang; Ruirui Chen; Xin Li; Youzhi Feng (European Journal of Soil Biology, 2025)

The hygienic insecticide dimefluthrin induced neurodevelopmental deficits and behavioral disorders in zebrafish (Danio rerio) larvae - Ruirui Li; Wenping Xu; Qingfeng Li; Jiagao Cheng; Zhong Li; Liming Tao; Yang Zhang (Environmental Research, 2025)

Auxiliary electrodialysis realizes over 50 times concentration of nuclide ions from liquid effluents of nuclear power plants - Zhenzhen Cui; Baoying Wang; Ruirui Li; Zihao Wang; Weicheng Fu; Junying Yan; Liang Wu; Yaoming Wang; Tongwen Xu (Desalination, 2025)

Heterogeneous Fenton-like catalysts of tetranitro iron phthalocyanine@Fe3O4@fly ash composites for fast decomposition of environmental contaminants - Dapeng Li; Peng Zhang; Yang Jin; Qing Li; Xinyuan Li; Ruirui Chang; Ruoxi Ma; Lin Yan; Suxiang Ge; Juntao Ma (Waste Disposal & Sustainable Energy, 2025)
Using fly ash (FA) solid wastes as economical carriers to construct Fenton-like catalytic composites with additional functions is more practical than the use of a single catalyst. Understanding the structure and properties of catalysts and carriers is vital to improve performance. Tetranitro iron phthalocyanine (TNFePc) is a highly active molecular catalyst, whose immobilization and Fenton-like heterogeneous catalysis remain unclear. In this study, magnetically recyclable composites of TNFePc@Fe 3 O 4 @FA were successfully fabricated. Further, Fe 3 O 4 nanocrystals decorated on FA surfaces could be used as special functional layer for composite recycling and simultaneous in situ TNFePc synthesis. Peroxides of H 2 O 2 , KHSO 5 , and tert-butyl hydrogen could be effectively activated by composites and transformed into highly reactive radicals. Moreover, molecular oxygen could be activated as well. Model pollutants, methylene blue and oxytetracycline, could be synergistically degraded by the radical oxidation of superoxide, hydroxyl, alkoxy, and sulfate radicals and non-radical oxidation of high-valent iron-oxo species of TNPcFe IV =O. To the best of our knowledge, this is the first design of FA-based composites with dual function, Fenton-like heterogeneous catalysis and magnetic recyclability, for environmental decontamination. Graphical abstract

Screening of Herbicides and Disturbance Effects upon Use of Benzonitrile Herbicide BOMS on Soil Microecology in Oat Field - Huan Liu; Jennifer Schug; Changning Li; Ruirui Yao; Guiqin Zhao; Yujie Niu (Journal of Soil Science and Plant Nutrition, 2025)

Transcriptome-Wide Analysis Revealed the Influential Role of PbrMTP (Metal Tolerance Protein) in the Growth and Fruit Development of Chinese White Pear - Ruirui Xu; Ahmad Ali; Ying Li; Xiao Zhang; Rahat Sharif; Xinxin Feng; Baopeng Ding (Journal of Plant Growth Regulation, 2025)

Erratum to “Did along-strike changes in continental subduction styles occur in the Dabie-Sulu orogenic belt?” [Journal of Structural Geology 191 (2025) 105321] - Ruirui Wang; Zhong-Hai Li; Qihua Cui; Zhiqin Xu (Journal of Structural Geology, 2025)

Did along-strike changes in continental subduction styles occur in the Dabie-Sulu orogenic belt? - Ruirui Wang; Zhong-Hai Li; Qihua Cui; Zhiqin Xu (Journal of Structural Geology, 2025)

The effect of stem contact fermentation on the quality of Cabernet Sauvignon and Merlot wines from Yantai, China - Ruirui Li; Dongyue Yang; Zhiyu Li; Xiaohong Tang; Ke Zhong; Yan Ding; Xiaomei Han; Xueqiang Guan; Yuxia Sun (Food Bioscience, 2025)

Bimetallic Bi–Sn nanoparticles in-situ anchored in carbon nanofiber as flexible self-supporting anode toward advanced magnesium ion batteries - Shaoqing Pan; Miao Cheng; Chen Ma; Huaijia Jing; Tongyu Shen; Jing Hu; Qianqian Liu; Tao Wei; Ruirui Wang; Wanfei Li; Bo Liu (Chemical Engineering Journal, 2025)

Selective oxidation of 2-methoxycyclohexanone to monomethyl adipate catalyzed by acidic ionic liquids - Yumei Liu; Kexin Li; Hasnain Nawaz; Ruirui Zhang; Min Ji; Ruixia Liu (Chemical Engineering Journal, 2025)

Innovative microbial activators for enhanced bioremediation of oil-contaminated soils: mechanistic insights - Yating Deng; Wujuan Sun; Yongbin Li; Jun Wei; Ruirui Rao; Qiongyu Cao; Sichang Wang; Qunzheng Zhang; Congyu Ke (World Journal of Microbiology and Biotechnology, 2025)

Hydrogen-rich water enhanced salt tolerance in tomato seedlings by regulating strigolactone biosynthesis genes SlMAX1 and SlD27 - Fujin Ye; Hua Fang; Li Feng; Meimei Shi; Ruirui Yang; Weibiao Liao (Plant and Soil, 2025)

Actinobacteria derived from soybean/corn intercropping influence the subsequent wheat - Songhe Chen; Ruirui Li; Bo Lv; Yanjun Li; Junda Li; Mengzhen Zhang; Xiaoxiao Ma; Cunhu Wang; Ruineng Xu; Yonghong Wang; Hong Liao; Yongjia Zhong (Agriculture, Ecosystems & Environment, 2025)

A comparative study of low-cost crude ureases extracted from multi-species of natural plant sources in enzyme-induced carbonate precipitation - Lingxiao Liu; Yaqing Gao; Xinwen Cao; Hao Meng; Zhanbin Wang; Yongshuai Qi; Ruirui Li; Jia He (Journal of Environmental Chemical Engineering, 2024)

Enhanced 2,4-dichlorophenol degradation by remodeling of crude soil microbial community structure using carbon-based immobilized microorganisms - Kangning Dong; Xiuxia Zhang; Lihan Ren; De Li; Kang Xiong; Ruirui Wang; Yupeng Zhang; Shuai Zuo (Journal of Environmental Chemical Engineering, 2024)

Urea amidolyase displayed on the surface of Saccharomyces cerevisiae for ethyl carbamate reduction in Chinese Huangjiu - Yupeng Wang; Qingbo Deng; Fangyuan Liu; Qian Li; Ruirui Li; Huan Wang; Chunhong Sun; Xinjian Wang; Xiaole Wu; Yefu Chen (Food Control, 2024)

Perfluoroalkyl substances exposure and the risk of breast cancer: A nested case-control study in Jinchang Cohort - Qian Dou; Yana Bai; Yongjun Li; Shan Zheng; Minzhen Wang; Zhongge Wang; Jianyun Sun; Desheng Zhang; Chun Yin; Li Ma; Yongbin Lu; Lizhen Zhang; et al. (Environmental Research, 2024)

Grape Seed Proanthocyanidins Protect Pancreatic β Cells Against Ferroptosis via the Nrf2 Pathway in Type 2 Diabetes - Haiyan Li; Haowei Zhang; Tongling Wang; Liyuan Zhang; Hao Wang; Heng Lu; Ruirui Yang; Yusong Ding (Biological Trace Element Research, 2024)
Pancreatic β cell damage is the primary contributor to type 2 diabetes mellitus (T2DM); however, the underlying mechanism remains nebulous. This study explored the role of ferroptosis in pancreatic β cell damage and the protective effects of grape seed proanthocyanidin extract (GSPE). In T2DM model rats, the blood glucose, water intake, urine volume, HbA1c, and homeostasis model assessment-insulin resistance were significantly increased, while the body weight and the insulin level were significantly decreased, indicating the successful establishment of the T2DM model. MIN6 mouse insulinoma β cells were cultured in high glucose and sodium palmitate conditions to obtain a glycolipid damage model, which was administered with GSPE, ferrostatin-1 (Fer-1), or nuclear factor erythroid 2-related factor 2 (Nrf2) small interfering (si) RNA. GSPE and Fer-1 treatment significantly improved pancreatic β-cell dysfunction and protected against cell death. Both treatments increased the superoxide dismutase and glutathione activity, reduced the malondialdehyde and reactive oxygen species levels, and improved iron metabolism. Furthermore, the treatments reversed the expression of ferroptosis markers cysteine/glutamate transporter (XCT) and glutathione peroxidase 4 (GPX4) caused by glycolipid toxicity. GSPE treatments activated the expression of Nrf2 and related proteins. These effects were reversed when co-transfected with si-Nrf2. GSPE inhibits ferroptosis by activating the Nrf2 signaling pathway, thus reducing β-cell damage and dysfunction in T2DM. Therefore, GSPE is a potential treatment strategy against T2DM. Graphical Abstract

Multi-field Coupling Simulation of Impact of Temperature and Density of Heat Injection Well on Carbon Budget during Hydrate Exploitation in Qilian Mountain Permafrost Region - Zhenhua Han; Ruirui Li; Luqing Zhang; Jian Zhou; Song Wang (Journal of Earth Science, 2024)

Anaerobic fermentation for hydrogen production and tetracycline degradation: Biodegradation mechanism and microbial community succession - Ruirui Shang; Wenhan Chen; Dong Wei; Xiang Li; Mengyao Tang; Zihao Yang; Yongfang Zhang (Science of The Total Environment, 2024)

Dissolved ammonia catalyzes proto-dolomite precipitation at Earth surface temperature - Ruirui Meng; Zuozhen Han; Xiao Gao; Yanyang Zhao; Chao Han; Yu Han; Renchao Yang; Shuangjian Li; Fang Liu; Maurice E. Tucker; Yanjing Chen (Earth and Planetary Science Letters, 2024)

Quenching-induced amorphisation and configuration transformation for the enhanced electrochemical performance of poly(vinylidene fluoride-hexafluoropropylene)-based solid electrolytes - Yaguang Zhang; Jianxun Zou; Ruirui Chang; Zixuan Min; Shuping Dong; Zhijia Tang; Xuandu Li; Jingjing Tang; Juan Yang; Xiangyang Zhou (Chemical Engineering Journal, 2024)

Fine-grained method for determining size and velocity distribution patterns of flat-fan nozzle-atomised droplets based on phase doppler interferometer - Ruirui Zhang; Peng Hu; Longlong Li; Qing Tang; Jiaxuan Yang; Jiajun Yang; Liping Chen (Computers and Electronics in Agriculture, 2024)

Natural pyrethrins induced developmental toxicity of zebrafish swim bladder in vivo and genotoxicity of lung cells in vitro - Ruirui Li; Cheng Zhang; Wenping Xu; Liming Tao; Jiagao Cheng; Zhong Li; Yang Zhang (Toxicology in Vitro, 2024)

Anthropogenic and climate impacts on carbon stocks of grassland ecosystems in Inner Mongolia and adjacent region - Xiaoping Xin; Xueqi Lan; Linghao Li; HuaJun Tang; Haonan Guo; Hui Li; Cuixia Jiang; Feng Liu; Changliang Shao; Yifei Qin; Zhonglin Liu; Gele Qing; et al. (Science of The Total Environment, 2024)

Divergent determinants on interannual variability of terrestrial water cycle across the globe - Jinyu Zhu; Dongqin Yin; Xiang Li; Ruirui Zhu; Hongxing Zheng (Science of The Total Environment, 2024)

Coordination-regulated epitaxial growth for 2D/3D perovskite vertical alignment heterostructure - Guoxiang Zhao; Yuan Chen; Shan Cong; Lutao Li; Chen Wang; Xinyu Du; Ruirui Liu; Jing Lu; Yu Liu; Gaoyuan Chen; Sihan Zhang; Liya Zhang; et al. (Science Bulletin, 2024)

Efficient extraction of lithium from alkaline solution using the synergistic extractants ethylhexyl salicylate and trialkylphosphine oxide in kerosene and stripping with acid - Zhonghua Niu; Licheng Zhang; Ruirui Liu; Yongquan Zhou; Lianmin Ji; Lijuan Li (Hydrometallurgy, 2024)

Synthesis of iron-manganese bimetallic materials supported by activated carbon and application of activated persulfate in the degradation of soil contaminated by crude oil - Jin Zheng; Chunyang Gao; Xianyuan Du; Hongkun Chen; Ruirui Han; Jiacai Xie; Dexun Zou; Quanwei Song; Zhansheng Wang; Xingchun Li (Environmental Research, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

Lithium-ion battery remaining useful life prediction: a federated learning-based approach - Ruirui Zhong; Bingtao Hu; Yixiong Feng; Shanhe Lou; Zhaoxi Hong; Fei Wang; Guangshen Li; Jianrong Tan (Energy, Ecology and Environment, 2024)

Cardiotoxicity risk induced by sanitary insecticide Dimefluthrin - Ruirui Li; Ning Zhou; Cheng Zhang; Mengqi Wu; Wenping Xu; Jiagao Cheng; Liming Tao; Zhong Li; Yang Zhang (Chemosphere, 2024)

Numerical simulation of agricultural unmanned helicopter corn canopy spraying - Qing Tang; Ruirui Zhang; Tongchuan Yi; Gang Xu; Longlong Li; Liping Chen (Computers and Electronics in Agriculture, 2024)

The crustal structure of southeast Tibet from joint inversion of surface wave dispersion and gravity anomaly data - Haopeng Chen; Ruirui Fan; Nanqiao Du; Feng Bao; Zeming Zhang; Xuelei Li; Fang Zou; Chuang Xu (Journal of Asian Earth Sciences, 2024)

Spillovers and dependency between green finance and traditional energy markets under different market conditions - Ruirui Wu; Bin Li; Zhongfeng Qin (Energy Policy, 2024)

Synthesis, structure-activity relationship and evaluation of antifungal activity of tryptanthrin derivatives against drug-resistant Candida albicans - Yandan Wu; Luyi Jiang; Ruina Liu; Lijiao Yang; Fei Zou; Tianyu Zhang; Zefei Fan; Tianbao Zhang; Huan Yang; Shuyun Yin; Ruirui Wang; Ganpeng Li; et al. (Medicinal Chemistry Research, 2024)

Screening and identification of reactive metabolic compounds of Cortex Periplocae based on glutathione capture-mass spectrometry - Guantong Yu; Ruirui Wang; Xiaomei Liu; Yuhong Li; Lin Li; Xiaoming Wang; Yuhong Huang; Guixiang Pan (Journal of Natural Medicines, 2024)

Numerical Determination of Anisotropic Permeability for Unconsolidated Hydrate Reservoir: A DEM–CFD Coupling Method - Ruirui Li; Zhenhua Han; Luqing Zhang; Jian Zhou; Song Wang; Fuyou Huang (Journal of Marine Science and Engineering, 2024)
Natural gas hydrate (NGH) is considered as a type of clean energy to replace coal and oil. During exploitation, permeability is one of the key parameters controlling production efficiency, reservoir stability, and greenhouse gas sequestration. Limited by experimental and numerical simulation tools, in current research, the directionality of permeability is usually ignored. In this work, a DEM–CFD coupling simulation method is developed to compute the anisotropic permeability. The sedimentary process of reservoir sediments is reconstructed, enabling the acquisition of numerical models that possess pore structures consistent with the actual fabric characteristics. The fluid transport process in various directions can be simulated with a finite element method. Taking the natural gas hydrate reservoir in the Shenhu area of the South China Sea as an example, the proposed method is validated and applied to explore the effect of compaction stress on permeability anisotropy. With the increase in compaction stress, the permeability anisotropy exhibited a rapid initial increase, followed by a sustained stabilization. The primary cause is the rearrangement of sediment particles. The non-spherical particles are driven to align in a predominantly horizontal orientation, thereby enhancing anisotropy. The proposed method provides a tool for the efficient exploitation of hydrate resources.

Granular activated carbon supported polyethylene glycol modified nano-zero-valent iron immobilized microbial removal of 2,4-dichlorophenol in water - Kangning Dong; Xiuxia Zhang; Kang Xiong; De Li; Lihan Ren; Yanyan Gao; Ruirui Wang; Shuai Zuo; Yupeng Zhang (Journal of Environmental Chemical Engineering, 2024)

Lamellar polyaniline-modified reduced graphene oxide loaded electron-rich Pd nanoparticles for highly efficient electrooxidation of C2 alcohols - Huan Zhang; Junhong Li; Xinyu Huang; Xuemin Duan; Ruirui Yue; Jingkun Xu (Fuel, 2024)

Multidimensional combinatorial screening for high-level production of erythritol in Yarrowia lipolytica - Lei Li; Qianqian Zhang; Ruirui Shi; Mingdong Yao; Kangming Tian; Fuping Lu; Hui-Min Qin (Bioresource Technology, 2024)

Construction of immobilized enzyme cascades for the biosynthesis of nucleotide sugars UDP-N-acetylglucosamine and UDP-glucuronic acid - Jialian Li; Yanlai Liu; Litao Hu; Ruirui Xu; Weijiao Zhang; Shan Hu; Yang Wang; Guocheng Du; Zhen Kang (Systems Microbiology and Biomanufacturing, 2024)

Effect of Hydrate Saturation on Permeability Anisotropy for Hydrate-Bearing Turbidite Sediments Based on Pore-Scale Seepage Simulation - Ruirui Li; Zhenhua Han; Luqing Zhang; Jian Zhou; Song Wang (Journal of Marine Science and Engineering, 2024)
The permeability of natural gas hydrate (NGH) turbidite reservoirs typically exhibits significant anisotropy, with anisotropy being a crucial basis for evaluating reservoir production. The presence of hydrates, as a crucial constituent of the solid framework, not only impacts the overall permeability but also influences the permeability anisotropy. To investigate the saturation sensitivity of permeability anisotropy, a series of simulations are performed by integrating particle flow and computational fluid dynamics methods to construct the homogeneous and layered numerical samples and compute the evolution of permeability anisotropy. It is shown that the permeability is isotropic for homogeneous sediments and the isotropy remains unchanged regardless of variations in hydrate saturation. The permeability of layered sediments, in contrast, exhibits significant anisotropy due to the presence of dominant channels within the coarse layer. For uniformly distributed hydrates, the more effective blockage in coarse layers results in a reduction in anisotropy. While for preferentially distributed hydrates, the excess blocking of coarse layers makes the dominant channels transfer to the fine layers, the further blocking causes a U-shaped anisotropy–saturation curve characterized by a decrease–increase transformation. During the reservoir production process, the preponderance channels blocked by hydrates will be cleared and the horizontal permeability will significantly increase. As a result, the production efficiency of horizontal wells may exceed expectations. The findings offer a parameter support for production estimation and environmental assessment.

Understanding the effect of plastic food packaging materials on food flavor: A critical review - Fuqing Bai; Guijie Chen; Yanan Hu; Yuexin Liu; Ruirui Yang; Junsheng Liu; Ruyan Hou; Hongfang Li; Xiaochun Wan; Huimei Cai (Trends in Food Science & Technology, 2024)

Interfacial hydrogen bond effect between CeO2 and g-C3N4 boosts conversion to adipic acid from aerobic oxidation of cyclohexane - Kexin Li; Bin He; Ruirui Wang; Ruiyi Yan; Ruirui Zhang; Ruixia Liu (Chemical Engineering Journal, 2024)

Enhanced the dehydrocyclization of 1,4-butanediol to γ-butyrolactone via the regulation of interface oxygen vacancies in Cu/MgO-CeO2 catalyst - Siying Chong; Shuang Zhao; Jiaoyan Li; Gangwei Huang; Yajing Zhang; Ruirui Liu; Kangjun Wang (Chemical Engineering Journal, 2024)

Potassium Permanganate/Persulfate Combined Oxidation Remediation of Petroleum Contaminated Soil - Xiuxia Zhang; Kangning Dong; Boyu Hao; Mingshan Ding; Shuai Zuo; Ruirui Wang; Ruyue Li (Water, Air, & Soil Pollution, 2024)

Shared xerophytic genes and their re‐use in local adaptation to aridity in the desert plant Gymnocarpos przewalskii - Ruirui Fu; Yuxiang Zhu; Ying Liu; Zhaoping Yang; Ruisen Lu; Yingxiong Qiu; Martin Lascoux; Pan Li; Jun Chen (Molecular Ecology, 2024)
In order to thrive and survive, plant species need to combine stability in the long term and rapid response to environmental challenges in the short term. The former would be reflected by parallel or convergent adaptation across species, and the latter by pronounced local adaptation among populations of the same species. In the present study, we generated a high‐quality genome and re‐sequenced 177 individuals for Gymnocarpos przewalskii , an important desert plant species from North‐West China, to detect local adaptation. We first focus on ancient adaptation to aridity at the molecular level by comparing the genomic data of 15 species that vary in their ability to withstand aridity. We found that a total of 118 genes were shared across xerophytic species but absent from non‐xerophytic species. Of the 65 found in G. przewalskii , 63 were under purifying selection and two under positive selection. We then focused on local adaptation. Up to 20% of the G. przewalskii genome showed signatures of local adaptation to aridity during population divergence. Thirteen of the selected shared xerophytic genes were reused in local adaptation after population differentiation. Hence, only about 20% of the genes shared and specific to xerophytic species and associated with adaptation to aridity were later recruited for local adaptation in G. przewalskii .

Thermal effects on rheological characteristics and its evolution mechanism of bio-modified rubberized asphalt for sustainable road system: A focus on rubber particle size - Tao Zhou; Lingwen Li; Ruirui Liu; Fangzhou Yu; Zejiao Dong (Journal of Cleaner Production, 2024)

Rare earth cation-modified X zeolites for isobutane alkylation: The influence of ionic radius - Zhiqiang Yang; Xinxin Li; Ruirui Zhang; Ruixia Liu (Fuel, 2024)

Metal coordination center mediated microenvironment regulation of cobalt sites on poly(ionic liquid)s enhance selective oxidation of cyclohexane conversion - Shengxin Chen; Bin He; Yingwei Li; Ruirui Wang; Ping Chen; Xingang Li; Ruixia Liu (Chemical Engineering Journal, 2024)

Large room-temperature electrocaloric response achieved by tailoring the first-order orthorhombic-tetragonal phase transition in BaTiO3-based ferroelectric ceramics - Ruirui Kang; Wenjing Qiao; Junjie Xiong; Haichao Hu; Ming Wu; Feng Li; Yangfei Gao; Lixue Zhang; Yingying Zhao; Xiaojie Lou (Chemical Engineering Journal, 2024)

Systematic Analysis of the Relationship Between Elevated Zinc and Epilepsy - Dadong Luo; Yaqing Liu; Junqiang Li; Xuhui Liu; Ruirui Zhang; Xuejuan Liu; Ningning Zhang; Wenzhao Zhang; Jiayi Liu; Lan Zhang; Tiancheng Wang (Journal of Molecular Neuroscience, 2024)

Mg Fe- layered double hydroxides (LDHs) modified electrode enhanced capacitive deionization for simultaneous phosphorus recovery and copper ions removal - Jingke Song; Chenyang Li; Xin Zhao; Ruirui Liu; Ruixue Han; Kai Jiang; Meiqing Shi; Dapeng Wu (Journal of Environmental Chemical Engineering, 2024)

Dissolved Mn2+ promotes microbially-catalyzed protodolomite precipitation in brackish oxidized water - Zuozhen Han; Jie Li; Yanyang Zhao; Qingyuan Chen; Xiao Gao; Kaiming Hu; Na Guo; Xiangyu Wei; Ruirui Meng; Chenlin Zhu; Maurice E. Tucker; Chao Han (Chemical Geology, 2024)

Geological structure identification of coalbed methane reservoir based on trend surface and curvature analysis algorithms - Guoxu Chen; Ruirui Li; Li Cao; Fang Lv; Jing Yuan; Panpan Li; Shengdong Liu; Zhongcheng Li (Earth Science Informatics, 2024)

Toward a remote sensing method based on commercial LiDAR sensors for the measurement of spray drift and potential drift reduction - Longlong Li; Ruirui Zhang; Liping Chen; Andrew J. Hewitt; Xiongkui He; Chenchen Ding; Qing Tang; Boqin Liu (Science of The Total Environment, 2024)

Construction of potassium cobalt iron cyanide double-hollow nanobubble prisms for high selective adsorption of cesium - Hangyu Wang; Chao Hu; Yifa Du; Ruirui Liu; Zhong Liu; Li Han; Yongquan Zhou (Journal of Water Process Engineering, 2024)

DNAzyme-driven bipedal DNA walker and catalytic hairpin assembly multistage signal amplified electrochemical biosensor based on porous AuNPs@Zr-MOF for detection of Pb2+ - Ruirui Liang; Jie Dong; Jiayi Li; Huali Jin; Min Wei; Tian Bai; Wenjie Ren; Yiwei Xu; Baoshan He; Zhiguang Suo (Food Chemistry, 2024)

Exosome-shuttled FTO from BM-MSCs contributes to cancer malignancy and chemoresistance in acute myeloid leukemia by inducing m6A-demethylation: A nano-based investigation - Ruirui Kou; Tian Li; Caizhu Fu; Duanfeng Jiang; Yue Wang; Jie Meng; Ruilan Zhong; Changjiu Liang; Min Dong (Environmental Research, 2024)

Identification of key factors affecting neonicotinoid residues in crops and risk of dietary exposure - Wenfei Yu; Ruxin Wu; Li Zhang; Yangzhong Pan; Jun Ling; Dan Yang; Jiajia Qu; Zhen Tao; Ruirui Meng; Yuexing Shen; Jingtong Yu; Nan Lin; et al. (Environmental Pollution, 2024)

Isolation methods, proliferation, and adipogenic differentiation of adipose-derived stem cells from different fat depots in bovines - Ruirui Zhu; Ye Feng; Ruirui Li; Kelong Wei; Yun Ma; Qingyou Liu; Deshun Shi; Jieping Huang (Molecular and Cellular Biochemistry, 2024)

ERS Mediated by GRP-78/PERK/CHOP Signaling Is Involved in Fluoride-Induced Ameloblast Apoptosis - Li Jinyi; Yang Keyu; Dai Shanshan; He Shuyang; Liu Ruirui; Guo Qingyu; Liu Fei (Biological Trace Element Research, 2024)

Bacterial interference competition and environmental filtering reduce the fungal taxonomic and functional contribution to plant residue decomposition in anoxic paddy soils - Yuanyuan Bao; Jan Dolfing; Xin Li; Ruirui Chen; Xiaodan Cui; Zhongpei Li; Xiangui Lin; Youzhi Feng (Soil and Tillage Research, 2024)

Response to “Comment on Magnetic tubular nickel@silica-graphene nanocomposites with high preconcentration capacity for organothiophosphate pesticide removal in environmental water: Fabrication, magnetic solid-phase extraction, and trace detection” [J. Hazard. Mater. 457 (2023) 131788] - Guoxin Wu; Ruirui Zhao; Xiangzi Li (Journal of Hazardous Materials, 2024)

Ionic liquids assisted synthesis of graphite carbon nitride for one-pot aerobic oxidation of cyclohexane to adipic acid - Kexin Li; Shuang Wei; Yumei Liu; Ruirui Wang; Ruirui Zhang; Ruixia Liu (Chemical Engineering Journal, 2024)

A magnetic pore-confined catalyst with ionic liquids supported on MOFs for the synthesis of aryl-oxazolidinones: design, performance, and recyclability - Siying Chong; Jiaoyan Li; Shuang Zhao; Gangwei Huang; Yajing Zhang; Ruirui Liu; Kangjun Wang (Chemical Engineering Journal, 2024)

Identification of point and nonpoint emission sources of neonicotinoid pollution in regional surface water - Yuanchen Chen; Jun Ling; Wenfei Yu; Li Zhang; Ruxin Wu; Dan Yang; Jiajia Qu; Hangbiao Jin; Zhen Tao; Yuexin Shen; Ruirui Meng; Jingtong Yu; et al. (Water Research, 2024)

Persistent free radicals generated from a range of biochars and their physiological effects on wheat seedlings - Ruirui Zhang; Andrew R. Zimmerman; Ruiling Zhang; Penghui Li; Yue Zheng; Bin Gao (Science of The Total Environment, 2024)

Eco-friendly synthesis of chemically cross-linked chitosan/cellulose nanocrystal/CMK-3 aerogel based shape-stable phase change material with enhanced energy conversion and storage - Miao Cheng; Yifan Yuan; Huaijia Jing; Jing Hu; Qianqian Liu; Tao Wei; Ruirui Wang; Wanfei Li; Bo Liu (Carbohydrate Polymers, 2024)

Single-step hydrothermal synthesis of biochar from waste industrial hemp stalk core for Pb2+ sorption: Characterization and mechanism studies - Zheren Zhang; Nengsheng Liu; Xiang Li; Yunzhu Wang; Yongkang Xiong; Ruirui Meng; Le Liu; Sufang He (Sustainable Chemistry and Pharmacy, 2023)

Metabolomics reveals antioxidant and antifungal functions of flavonoids in the early stage wounded potato tubers - Xiaoyuan Zheng; Xuejiao Zhang; Jinmei Zhao; Ruirui Yang; Lu Bai; Yongcai Li; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2023)

Application of genomic markers generated for ray-finned fishes in chondrichthyan Phylogenomics - Shengyong Xu; Ruirui Zhao; Shanshan Cai; Pengfei Li; Zhiqiang Han (Organisms Diversity & Evolution, 2023)

Exosomal circCNOT6L Regulates Astrocyte Apoptotic Signals Induced by Hypoxia Exposure Through miR99a-5p/SERPINE1 and Alleviates Ischemic Stroke Injury - Wanting He; Lian Gu; Jialei Yang; Ruirui Zhang; Jianxiong Long; Wenyi Peng; Baoyun Liang; Lulu Zhu; Miao Lv; Aruo Nan; Li Su (Molecular Neurobiology, 2023)

Assessment of genetic diversity of Prunus salicina 'Shazikongxinli' by morphological traits and molecular markers - Gui Wang; Ruirui Li; Maohong Wu; Feihong Ren; Lili Wang; Guang Qiao (Genetic Resources and Crop Evolution, 2023)

Food-borne botulism from homemade sauce leading to cardiac arrest: A family case series with literature review - Weiying Yang; Dongyue Jiang; Ruirui Li; Lichao Sun (Toxicon, 2023)

The higher the cuteness the more it inspires garbage sorting intention? - Fuqiang Tan; TingYue Kuang; DaJun Yang; Zemin Jia; RuiRui Li; Liangyu Wang (Journal of Cleaner Production, 2023)

Design and experiment of a binocular vision-based canopy volume extraction system for precision pesticide application by UAVs - Ruirui Zhang; Shuaikai Lian; Longlong Li; Linhuan Zhang; Chaocheng Zhang; Liping Chen (Computers and Electronics in Agriculture, 2023)

Discovery of deguelin derivatives in combination with fluconazole against drug-resistant Candida albicans - Biaoqi Liu; Youwei Wu; Dingmei Qin; Hairong Wang; Hongjie Chen; Yi Zhang; Weilie Xiao; Xiaoli Li; Ruirui Wang; Ruihan Zhang (Medicinal Chemistry Research, 2023)

CoupleUNet: Swin Transformer coupling CNNs makes strong contextual encoders for VHR image road extraction - Ruirui Li; Tao Chen; Yiran Liu; Haoyu Jiang (International Journal of Remote Sensing, 2023)

Ferulic acid treatment enhances the synthesis, transport and deposition of suberin polyaliphatic monomers on potato tuber wounds - Ruirui Yang; Ye Han; Xuejiao Zhang; Qihui Wang; Xiaoyuan Zheng; Ying Wang; Yongcai Li; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2023)

Fabrication and application of molecularly imprinted polymer doped carbon dots coated silica stationary phase - Peijun Chai; Xuhui Geng; Ruirui Zhu; Wenpu Wu; Xuesong Wang; Jinhua Li; Longwen Fu; Hongdan Wang; Wanhui Liu; Lingxin Chen; Zhihua Song (Analytica Chimica Acta, 2023)

A cascade electro-dehydration process for simultaneous extraction and enrichment of uranium from simulated seawater - Ruirui Li; Huangying Wang; Junying Yan; Rong Fu; Baoying Wang; Chenxiao Jiang; Yaoming Wang; Tongwen Xu (Water Research, 2023)

A direct electrochemical substitution electrodialytic system for CO2 conversion into high value-added soda - Huangying Wang; Haiyang Yan; Kang Peng; Junying Yan; Rong Fu; Ruirui Li; Baoying Wang; Chenxiao Jiang; Yaoming Wang; Tongwen Xu (Chemical Engineering Journal, 2023)

Facile treatment of municipal solid waste incineration fly ash by one-step microwave hydrothermal method: Hazards detoxification and tobermorite synthesis - Ruirui Yuan; Xiaohui Fan; Min Gan; Qianqian Zhao; Siping Lu; Shixian Li (Journal of Environmental Chemical Engineering, 2023)

Trade-off between microbial ecophysiological features regulated by soil fertility governs plant residue decomposition - Yuanyuan Bao; Jan Dolfing; Ruirui Chen; Zhongpei Li; Xiangui Lin; Youzhi Feng (Soil and Tillage Research, 2023)

UV-C irradiation maintains cell membrane integrity at wounds of potato tubers during healing by regulating ROS homeostasis and increasing antioxidant activity - Xuejiao Zhang; Xiaoyuan Zheng; Ye Han; Ruirui Yang; Qihui Wang; Di Gong; Yongcai Li; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2023)

Ion transmembrane behaviors in selective electrodialysis for acid recovery: Impact of ion categories - Junying Yan; Huangying Wang; Haiyang Yan; Ruirui Li; Rong Fu; Weicheng Fu; Liang Ge; Baoying Wang; Yaoming Wang; Tongwen Xu (Desalination, 2023)

Melatonin facilitates the deposition of suberin polyphenolic and lignin at wounds of potato tubers by mediating nitric oxide and reactive oxygen species - Qihui Wang; Ye Han; Ruirui Yang; Xuejiao Zhang; Yatong Zhu; William Oyom; Yongcai Li; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2023)

Distribution and exposure risk assessment of chlorinated paraffins and novel brominated flame retardants in toys - Ruirui Zhang; Juan Li; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2023)

Lacustrine-evaporitic microbial dolomite from a Plio-Pleistocene succession recovered by the SG-1 borehole in the Qaidam Basin, NE Tibetan Plateau - Yanyang Zhao; Xiangyu Wei; Zuozhen Han; Chao Han; Xiao Gao; Ruirui Meng; Qiyu Wang; Maurice E. Tucker; Minghui Li; Mónica Sánchez-Román (Chemical Geology, 2023)

Identification and genetic analysis of major gene ST3GAL4 related to serum alkaline phosphatase in chicken - Hehe Tang; Yanchao Ma; Jianzeng Li; Zhenzhen Zhang; Wenting Li; Chunxia Cai; Lujie Zhang; Zhuanjian Li; Yadong Tian; Yanhua Zhang; Jinqing Ji; Lu Han; et al. (Research in Veterinary Science, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

TBM penetration rate prediction ensemble model based on full-scale linear cutting test - Yaxu Wang; Jiwen Wang; Ruirui Wang; Bin Liu; Yao Li (Tunnelling and Underground Space Technology, 2023)

Determination of potential thresholds for N-ethyl-N-nitrosourea and ethyl methanesulfonate based on a multi-endpoint genotoxicity assessment platform in rats - Xuejiao Zhu; Jiao Huo; Zhu Zeng; Yunjie Liu; Ruirui Li; Yiyi Chen; Lishi Zhang; Jinyao Chen (Environmental Science and Pollution Research, 2022)
The main goal of the study was to investigate the genotoxic response of N-ethyl-N-nitrosourea (ENU) and ethyl methanesulfonate (EMS) at low doses in a multi-endpoint genotoxicity assessment platform in rats and to derive potential thresholds and related metrics. Male Sprague–Dawley rats were treated by daily oral gavage for 28 consecutive days with ENU (0.25 ~ 8 mg/kg bw) and EMS (5 ~ 160 mg/kg bw), both with six closely spaced dose levels. Pig-a gene mutation assay, micronucleus test, and comet assay were performed in several timepoints. Then, the dose–response relationships were analyzed for possible points of departure (PoD) using the no observed genotoxic effect level and benchmark dose (BMD) protocols with different critical effect sizes (CES, 0.05, 0.1, 0.5, and 1SD). Overall, dose-dependent increases in all investigated endpoints were found for ENU and EMS. PoDs varied across genetic endpoints, timepoints, and statistical methods, and selecting an appropriate lower 95% confidence limit of BMD needs a comprehensive consideration of the mode of action of chemicals, the characteristics of tests, and the model fitting methods. Under the experimental conditions, the PoDs of ENU and EMS were 0.0036 mg/kg bw and 1.7 mg/kg bw, respectively.

Bioremediation of petroleum hydrocarbon contaminated soil by microorganisms immobilized on sludge modified by non-ionic surfactant - Junlong Yu; Ruyue Li; Xiuxia Zhang; Yi Du; Ruojun Ma; Xiaodong Zhao; Shuai Zuo; Kangning Dong; Ruirui Wang; Yupeng Zhang; Yingying Gu; Juan Sun (Environmental Science and Pollution Research, 2022)

Association between short-term exposure to ambient air pollution and number of outpatient Helicobacter pylori infection visits - Lizuo Ma; Zhijing Lin; Jiaoxue Wang; Ruirui Ye; Yuefang Li; Ping Chen; Zhi Yuan; Liyan Yang; Lin Miao; Jiehua Li (Environmental Science and Pollution Research, 2022)

Monitoring of Air Pollution by Remote Sensing in Lanzhou City from 2010 to 2019 - Tianzhen Ju; Zhuohong Liang; Wenjun Liu; Bingnan Li; Ruirui Huang; Tunyang Geng (Water, Air, & Soil Pollution, 2022)

sVCAM1 in the Hippocampus Contributes to Postoperative Cognitive Dysfunction in Mice by Inducing Microglial Activation Through the VLA-4 Receptor - Chenglong Li; Qi Li; Shuai Liu; Jiaying Li; Wei Yu; Yan Li; Ruirui Zhang; Sihua Qi (Molecular Neurobiology, 2022)

Reshaping of the soil microbiome by the expansion of invasive plants: shifts in structure, diversity, co-occurrence, niche breadth, and assembly processes - Changchao Li; Huaizhi Bo; Bingzhong Song; Xiaocui Chen; Qingqing Cao; Ruirui Yang; Shuping Ji; Lifei Wang; Jian Liu (Plant and Soil, 2022)

Genomic Comparison and Genetic Marker Identification of the White-Spotted Bamboo Shark Chiloscyllium plagiosum - Ruirui Zhao; Shanshan Cai; Dingfang Lu; Pengfei Li; Shengyong Xu; Yuan Li (Frontiers in Marine Science, 2022)
The white-spotted bamboo shark ( Chiloscyllium plagiosum ) is an ecologically and commercially important marine cartilaginous fish in the Indo-Western Pacific. However, the resources of this species are declining in recent years due to habitat degradation and overfishing. Studies on genomics and genetic markers can provide valuable information for sound management and conservation of C. plagiosum . In this study, genome resequencing data of a domesticated C. plagiosum individual were generated for genomic comparison between wild and domesticated samples. Based on 281.17 Gb of clean sequencing data, the genome size of the domesticated sample was estimated as 4.99 Gb, with heterozygosity of 0.51% and repeat ratio of 74.67%, which is about 1 Gb larger than that of the wild sample (3.85 Gb with a repeat ratio of 63.53%). By using a reference-based approach, we assembled a nearly 3.45 Gb genome sequence of the domesticated sample, with the scaffold N50 of 69.45 Mb. Subsequent identification of genome-wide microsatellite markers confirmed the different abundance of repeat elements in wild and domesticated C. plagiosum . Additionally, a total of 8,703,211 single-nucleotide polymorphisms (SNPs) were detected and annotated. The demographic analysis based on identified SNPs revealed a large and constant effective population size of C. plagiosum after the last population expansion (~0.3 million years ago). The genomic data and identified genetic markers in this study can provide fundamental and useful information for further comparative genomics, evolutionary biology, and conservation genetics of C. plagiosum .

Multifractal Investigation on Multi-scale Pore Structure Heterogeneity of High Rank Coal Reservoirs - Ruirui Li; Xiaowei Hou; Luwang Chen; Huihuang Fang; Chunshan Zheng (Natural Resources Research, 2022)

Analysis and research of absorbing aerosols in Beijing-Tianjin-Hebei region - TianZhen Ju; JiaLe Duan; BingNan Li; HaiYan Gao; JiaChen Fan; ZhuoHong Liang; RuiRui Huang; TunYang Geng (Air Quality, Atmosphere & Health, 2022)

Apigenin inhibits growth of melanoma by suppressing miR-512-3p and promoting the G1 phase of cell cycle involving the p27 Kip1 protein - Qun Xie; Ruirui Zhang; Dandan Liu; Jing Yang; Qiang Hu; Chao Shan; Xiaohan Li (Molecular and Cellular Biochemistry, 2022)

Stocking rate changed the magnitude of carbon sequestration and flow within the plant-soil system of a meadow steppe ecosystem - Dongyan Jin; Ruirui Yan; Linghao Li; Jiaguo Qi; Jiquan Chen; Hongbin Xu; Yuchun Yan; Xiaoping Xin (Plant and Soil, 2022)

Effects of stocking rate on the interannual patterns of ecosystem biomass and soil nitrogen mineralization in a meadow steppe of northeast China - Yu Zhang; Jinling Zhao; Xiaoping Xin; Miao Wang; Fengjuan Pan; Ruirui Yan; Linghao Li (Plant and Soil, 2022)

Predicting acupuncture efficacy for functional dyspepsia based on routine clinical features: a machine learning study in the framework of predictive, preventive, and personalized medicine - Tao Yin; Hui Zheng; Tingting Ma; Xiaoping Tian; Jing Xu; Ying Li; Lei Lan; Mailan Liu; Ruirui Sun; Yong Tang; Fanrong Liang; Fang Zeng (EPMA Journal, 2022)

Effects of grazing intensity on soil nematode community structure and function in different soil layers in a meadow steppe - Fengjuan Pan; Ruirui Yan; Jinling Zhao; Linghao Li; Yanfeng Hu; Ye Jiang; Jie Shen; Neil B. McLaughlin; Dan Zhao; Xiaoping Xin (Plant and Soil, 2022)

Spatiotemporal variations and pollution sources of HCHO over Jiangsu-Zhejiang-Shanghai based on OMI - Tianzhen Ju; Jiachen Fan; Xin Liu; Yulin Li; Jiale Duan; Ruirui Huang; Tunyang Geng; Zhuohong Liang (Air Quality, Atmosphere & Health, 2022)

The severe toxicity of CuO nanoparticles to the photosynthesis of the prokaryotic algae Arthrospira sp - Xingkai Che; Ruirui Ding; Qiang Zhang; Yujie Li; Qi Sun; Yuting Li; Zishan Zhang; Wei Wang; Huiyuan Gao (Environmental Science and Pollution Research, 2021)

Construction of high density genetic map and QTL mapping in sorghum × sudangrass - Peng Jin; Lihua Wang; Wenjie Zhao; Jian Zheng; Yi-Hong Wang; Yanlong Liu; Ruirui Meng; Jichao Dai; Lei Zhou; Jieqin Li (Euphytica, 2021)

Absorbable aerosols based on OMI data: a case study in three provinces of Northeast China - Jiale Duan; Tianzhen Ju; Qinhua Wang; Fengshuai Li; Jiachen Fan; Ruirui Huang; Zhuohong Liang; Guoqaing Zhang; Tunyang Geng (Environmental Monitoring and Assessment, 2021)

Black phosphorus nanosheets and docetaxel micelles co-incorporated thermoreversible hydrogel for combination chemo-photodynamic therapy - Ruirui Li; Linwei Shan; Yanan Yao; Feifei Peng; Shanshan Jiang; Dandan Yang; Guixia Ling; Peng Zhang (Drug Delivery and Translational Research, 2021)

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

Antisense oligonucleotide technology can be used to investigate a circular but not linear RNA-mediated function for its encoded gene locus - Zhenxing Song; Ruirui Jia; Mingfeng Tang; Fei Xia; Haiyang Xu; Zhengguo Li; Chuan Huang (Science China Life Sciences, 2021)

Factors controlling organic carbon distributions in a riverine wetland - Junyu Dong; Di Zhao; Chao Zhang; Qingqing Cao; Jiaohui Fang; Ruirui Yang; Shuping Ji; Changchao Li; Ruiqi Zhao; Jian Liu (Environmental Science and Pollution Research, 2020)

Functional community composition has less environmental variability than taxonomic composition in straw-degrading bacteria - Yuanyuan Bao; Zhiying Guo; Ruirui Chen; Meng Wu; Zhongpei Li; Xiangui Lin; Youzhi Feng (Biology and Fertility of Soils, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

Differences of the microbial community structures and predicted metabolic potentials in the lake, river, and wetland sediments in Dongping Lake Basin - Jiaohui Fang; Ruirui Yang; Qingqing Cao; Junyu Dong; Changchao Li; Quan Quan; Miansong Huang; Jian Liu (Environmental Science and Pollution Research, 2020)

Overexpression of wheat α-mannosidase gene TaMP impairs salt tolerance in transgenic Brachypodium distachyon - Wenlong Wang; Yunzhen Wu; Ruirui Shi; Mengwei Sun; Qinxue Li; Guangqiang Zhang; Jiajie Wu; Yong Wang; Wei Wang (Plant Cell Reports, 2020)

A mechanical method for predicting TBM penetration rates - Ruirui Wang; Xu Guo; Jianbin Li; Jian Wang; Liujie Jing; Zhengyu Liu; Xinji Xu (Arabian Journal of Geosciences, 2020)

A simple and low-energy method to prepare loratadine nanosuspensions for oral bioavailability improvement: preparation, characterization, and in vivo evaluation - Dandan Yang; Ruirui Li; Fang Zhang; Li Qin; Feifei Peng; Shanshan Jiang; Huiyang He; Xiumei Lu; Peng Zhang (Drug Delivery and Translational Research, 2020)

Effects of different inhibitors such as malonic acid, Na3PO4 and HgCl2 on uptake of different forms of antimony in rice plant - RenWei Feng; Lei Lei; BiXiu Liu; WenXiang Chen; RuiRui Zhang; LiZhen Wang; YuanPing Li; JunMing Su; JiaXin Dai; RenJie Wang; ZiTing Lin; Ibtissem Ben Fekih; et al. (Plant and Soil, 2019)

Source apportionment and health risk assessment of trace elements in the heavy industry areas of Tangshan, China - Ruirui Si; Jinyuan Xin; Wenyu Zhang; Shihong Li; Tianxue Wen; Yuesi Wang; Yining Ma; Zirui Liu; Xiaojuan Xu; Miaoling Li; Guangjing Liu (Air Quality, Atmosphere & Health, 2019)

Effects of Antibiotics on Microbial Communities Responsible for Perchlorate Degradation - Xiaoxuan Zheng; Bo Jiang; Hang Lang; Ruirui Zhang; Yiqiang Li; Yingnan Bian; Xiangyu Guan (Water, Air, & Soil Pollution, 2019)

ABA signaling rather than ABA metabolism is involved in trehalose-induced drought tolerance in tomato plants - Wenqing Yu; Ruirui Zhao; Liu Wang; Shujuan Zhang; Rui Li; Jiping Sheng; Lin Shen (Planta, 2019)

Genetic mapping of powdery mildew resistance genes in soybean by high-throughput genome-wide sequencing - Bingzhi Jiang; Mu Li; Yanbo Cheng; Zhandong Cai; Qibin Ma; Ze Jiang; Ruirui Ma; Qiuju Xia; Gengyun Zhang; Hai Nian (Theoretical and Applied Genetics, 2019)

Ghrelin Promotes Cortical Neurites Growth in Late Stage After Oxygen-Glucose Deprivation/Reperfusion Injury - Jing Liu; Man Chen; Ruirui Dong; Changwei Sun; Shuo Li; Shigong Zhu (Journal of Molecular Neuroscience, 2019)

Bacterial communities involved directly or indirectly in the anaerobic degradation of cellulose - Yuanyuan Bao; Jan Dolfing; Baozhan Wang; Ruirui Chen; Miansong Huang; Zhongpei Li; Xiangui Lin; Youzhi Feng (Biology and Fertility of Soils, 2019)

Mapping daily leaf area index at 30 m resolution over a meadow steppe area by fusing Landsat, Sentinel-2A and MODIS data - Zhenwang Li; Chengquan Huang; Zhiliang Zhu; Feng Gao; Huan Tang; Xiaoping Xin; Lei Ding; Beibei Shen; Jinxun Liu; Baorui Chen; Xu Wang; Ruirui Yan (International Journal of Remote Sensing, 2018)

Insight into Bacterial Community Diversity and Monthly Fluctuations of Medicago sativa Rhizosphere Soil in Response to Hydrogen Gas Using Illumina High-Throughput Sequencing - Zhiying Li; Xin Liu; Ruirui Liu; Lulu Li; Lin Wang; Weiwei Wang (Current Microbiology, 2018)

Two key features influencing community assembly processes at regional scale: Initial state and degree of change in environmental conditions - Youzhi Feng; Ruirui Chen; James C. Stegen; Zhiying Guo; Jianwei Zhang; Zhongpei Li; Xiangui Lin (Molecular Ecology, 2018)
Belowground microbial communities strongly influence ecosystem function such that predicting function may rely on understanding ecological processes that assemble communities. Uncertainty remains, however, in what governs the relative contributions of different ecological processes. To help fill this knowledge gap, we test the general hypothesis that both initial state and degree of change in environmental conditions govern the relative contributions of different ecological assembly processes. To do so, we leveraged regional‐scale nutrient and organic matter addition experiments and used soil organic matter (SOM) as a proxy of integrated soil environmental conditions. Consistent with our hypothesis, we found that both the initial amount of SOM and the degree of change in SOM—in response to nutrient addition—influenced the relative contributions of different ecological assembly processes. These influences were most clearly observed at the regional scale, suggesting potential scale dependence. More specifically, nutrient additions homogenized bacterial community composition due to enhanced influences of homogenizing dispersal when SOM content was initially high. In contrast, nutrient additions led to divergence in community composition due to variable selection when initial SOM was low and/or when SOM increased significantly in response to nutrient additions. Our findings indicate important connections among initial conditions, degree of change in environmental variables and microbial community assembly processes that may influence ecosystem processes. These conceptual inferences highlight a need to strengthen connections between ecological theory and biogeochemical modelling.

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

Application of the CRISPR/Cas9 system in Dioscorea zingiberensis - Shan Feng; Wei Song; Ruirui Fu; Hong Zhang; Anran Xu; Jiaru Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Enhanced drought tolerance in tomato plants by overexpression of SlMAPK1 - Liu Wang; Ruirui Zhao; Rui Li; Wenqing Yu; Meijing Yang; Jiping Sheng; Lin Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

A comparison of amorphous calcium carbonate crystallization in aqueous solutions of MgCl2 and MgSO4: implications for paleo-ocean chemistry - Mei Han; Yanyang Zhao; Hui Zhao; Zuozhen Han; Huaxiao Yan; Bin Sun; Ruirui Meng; Dingxiang Zhuang; Dan Li; Binwei Liu (Mineralogy and Petrology, 2018)

Effects of heavy metal pollution on enzyme activities in railway cut slope soils - Xiaoyi Meng; Yingwei Ai; Ruirui Li; Wenjuan Zhang (Environmental Monitoring and Assessment, 2018)

Calcium carbonate precipitation by Synechocystis sp. PCC6803 at different Mg/Ca molar ratios under the laboratory condition - Zuozhen Han; Ruirui Meng; Huaxiao Yan; Hui Zhao; Mei Han; Yanyang Zhao; Bin Sun; Yanbiao Sun; Jie Wang; Dingxiang Zhuang; Wenjun Li; Lingxue Lu (Carbonates and Evaporites, 2017)

MiR-340 Regulates Fibrinolysis and Axon Regrowth Following Sciatic Nerve Injury - Shiying Li; Ruirui Zhang; Ying Yuan; Sheng Yi; Qianqian Chen; Leilei Gong; Jie Liu; Fei Ding; Zheng Cao; Xiaosong Gu (Molecular Neurobiology, 2017)

Diversity of Eukaryotic Algae in Propylene Oxide Saponification Wastewater Activated Sludge - Rong He; Xiangyu Fan; Pengfei Gu; Yan Ji; Junyu Shen; Ruirui Li; Yumei Li; Qiang Li (Water Conservation Science and Engineering, 2017)

Global identification and expression analysis of stress-responsive genes of the Argonaute family in apple - Ruirui Xu; Caiyun Liu; Ning Li; Shizhong Zhang (Molecular Genetics and Genomics, 2016)

Comparison of two inversion methods for leaf area index using HJ-1 satellite data in a temperate meadow steppe - Qiong Wu; Yunxiang Jin; Yuhai Bao; Quansheng Hai; Ruirui Yan; Baorui Chen; Hongbin Zhang; Baohui Zhang; Zhenwang Li; Xiaoyu Li; Xiaoping Xin (International Journal of Remote Sensing, 2015)

Feasibility of human hair follicle-derived mesenchymal stem cells/CultiSpher®-G constructs in regenerative medicine - Pengdong Li; Feilin Liu; Chunling Wu; Wenyue Jiang; Guifang Zhao; Li Liu; Tingting Bai; Li Wang; Yixu Jiang; Lili Guo; Xiaojuan Qi; Junna Kou; et al. (Cell and Tissue Research, 2015)

Chimeric DNA vaccines encoding Eimeria acervulina macrophage migration inhibitory factor (E.MIF) induce partial protection against experimental Eimeria infection - Xiaokai Song; Ruirui Zhang; Lixin Xu; Ruofeng Yan; Xiangrui Li (Acta Parasitologica, 2015)
Chimeric DNA vaccines co-expressing Eimeria acervulina macrophage migration inhibitory factor (E.MIF) and chicken IL-2 (IL-2) or interferon-γ (IFN-γ) were constructed and their efficacies against E. acervulina were evaluated. The open reading frame (ORF) of E.MIF was cloned from E. acervulina merozoites and subcloned into the eukaryotic expression vector pVAX1 with chicken cytokine gene IFN-γ or IL-2 to construct the DNA vaccines pVAX-E.MIF-IFN-γ, pVAX-E.MIF-IL-2 and pVAX-E.MIF. The in vivo transfection of the target genes was detected by use of reverse transcription polymerase chain reaction (RT-PCR) and Western blot. Immunizations were carried out by vaccinating chickens twice with a dose rate of 100 μg intramuscularly. Seven days post second immunization, all chickens except the unchallenged control group were challenged orally with 1 × 105 sporulated oocysts of E. acervulina. Seven days later, the duodenum was collected. The results showed that the target genes were expressed effectively in vivo. DNA vaccines and the recombinant E.MIF protein could alleviate body weight loss and duodenal lesions significantly compared to the control groups. Furthermore, pVAX-E.MIF-IL-2 and pVAX-E.MIF-IFN-γ induced anticoccidial indexs (ACIs) of 179.12 and 170, respectively, which were significantly higher than that of pVAX-E.MIF (ACI = 162.31). Our results demonstrated that E.MIF is a potential vaccine candidate against E. acervulina and chicken IFN-γ or IL- 2 may be used as genetic adjuvants to improve the efficacies of DNA vaccines against avian coccidiosis.

Genomewide analysis of TCP transcription factor gene family in Malus domestica - RUIRUI XU; PENG SUN; FENGJUAN JIA; LONGTAO LU; YUANYUAN LI; SHIZHONG ZHANG; JINGUANG HUANG (Journal of Genetics, 2014)

Association study of a common genetic variant in pre-miR-1596 with chicken performance traits - Hong Li; Yadong Tian; Guirong Sun; Xiaojun Liu; Ruirui Jiang; Ruili Han; Guoxi Li; Xiangtao Kang (Molecular Biology Reports, 2014)

Genome-wide identification and phylogenetic analysis of Family-1 UDP glycosyltransferases in maize (Zea mays) - Yanjie Li; Pan Li; Yong Wang; Ruirui Dong; Huimin Yu; Bingkai Hou (Planta, 2014)

Cloning of TPO gene and associations of polymorphisms with chicken growth and carcass traits - Xinyan Hou; Ruili Han; Yadong Tian; Wanying Xie; Guirong Sun; Guoxi Li; Ruirui Jiang; Xiangtao Kang (Molecular Biology Reports, 2013)

Biodegradation of Phenanthrene by a Halophilic Bacterial Consortium Under Aerobic Conditions - Baisuo Zhao; Hui Wang; Xinwei Mao; Ruirui Li (Current Microbiology, 2009)